The Potential of Anting – Anting (Acalypha indica L.) Leaf Extract as Anti-Scabies to Sarcoptes scabiei var. Cuniculi in vitro - Luluk Tri Astuti; Rahmi Sugihartuti; Lianny Nagoi; Nunuk Dyah Retno Lastuti; Dewa Ketut Meles; Agus Sunarso (Journal of Parasite Science (JoPS), 2019)
The Aim of research to determine the potential of anting-anting (Acalypha indica L.) leaf extract as anti-scabies to Sarcoptes scabiei var. Cuniculi in vitro by observing the mortality rates and lethal concentration of Sarcoptes scabiei. There were 5 treatments namely DMSO 0.5% (PN). Amitraz (P0), anting-anting (Acalypha indica L.) leaf extract concentratrion of 6,25% (P1), 12,5% (P2) and 25% (P3). Observations were carried out for 8 hours with stereomicroscope. The data  was analyzed using rpobit analysis with SPSS 20.0 software. The results showed that the fastest mortality rate of S. Scabiei was group p3 at 4.6 mites/hour., then P0, P2, P1 and PN respectively 3.5, 3.1, 1.9, and 1.3 mites/ hour. The smallest concentration of anting-anting (Acalypha indica L.) leaf extract was not significantly different compared to amitraz  for killing of 50% and 90% S. Scabiei was 12.5% with lethal time (LT50) 1.82 hours and (LT90) 3.69 hours. In conclusion, anting-anting (Acalypha indica L.) leaf extract has mortality rate against S. Scabiei var. Cuniculi of 3.1 mites/hour, lethal concentration of 12.5% and potential as anti-scabies in vitro.